HAMA PADA TEGAKAN JATI ( Tectona grandis L.f ) DI DESA TALAGA KECAMATAN DAMPELAS KABUPATEN DONGGALA - Hidayat, Rahmat; Yusran, Yusran; Irmasari, Irmasari (Jurnal Warta Rimba, 2014)
Jati (Tectona grandis L. f) be one of the tropical plants that has economical value tall, because the wood belongs to multipurpose wood. teak can be used to various also dekoratif technique need. The natural distribution found at Indians, Burma and Thailand. In Iindonesia found at java, Kangean, Bali, Muna, Buton, Maluku, Sumbawa and Lampung. teak development at district dampelas planted according to monokultur in vast scale. This watchfulness activity aims to detect pest kinds, attack phenomenon, also pest attack intensity in strightened Jati (T. grandis l. f) at village Talaga district Dampelas regency Donggala. Watchfulness result demoes that pest kinds that assault strightened teak melokasi watchfulness tree termite (Neotermes tectonae), Dry wood termite (Crytotermes spp.), Plantlice (Aphis sp.), Grasshopper (Valanga nigricornis Burn), Black ant (Fuliginosus Lasius),Â  and Shakies (Duomitus Ceramicus). temporary pest attack frequency in strightened teak as big as 88,2% with attack intensity 34,9% and pest attack consequence teak strightened damage criteria damage. Keywords : Stands, Strightened, Tectona grandis L.f. Districts, Dampelas